Good governance and multidimensional poverty: a comparative analysis of 71 countries - Jindra, C; Vaz, A (Wiley, 2019)
In 2015, the international community committed to ‘reduce at least by half the proportion of men, women and children of all ages living in poverty in all its dimensions’. According to international development agencies, good governance is crucial to achieve this. We examine the relationship between good governance and multidimensional poverty using hierarchical models and survey data for 71 countries. Our results suggest there is a direct effect of good governance on multidimensional poverty and that good governance is associated with reduced horizontal inequalities. However, we find evidence of a beneficial effect of good governance for middle income countries but not for low income countries. Thus while our results suggest that good governance can play a role in reducing multidimensional poverty, they also suggest that governance reforms alone might not yield the desired effect for all countries.